Limited seed dispersability in a megadiverse OCBIL grassland - Arruda, Andre J; Junqueira, Patricia A; Rodrigues, Hanna T S; Yvanez, Florian; Poschlod, Peter; Silveira, Fernando A O; Buisson, Elise (Biological journal of the Linnean Society, 2021)
Species from OCBILs (old, climatically buffered, infertile landscapes) are expected to exhibit reduced dispersability, linked to long-term stable environmental conditions. We tested the prediction of limited dispersability in plant communities in campo rupestre, a megadiverse OCBIL grassland. In a field experiment, we sampled sticky and funnel traps for 12 months along paired preserved and disturbed plots to estimate and compare annual seed density and richness. Our community-level seed rain assessment suggested widespread seed limitation in both preserved and disturbed areas, expressed by the low seed density in traps (average of 2.6 seeds/m2/day) and remarkably low seed density found for 90% of the morphospecies. Although seed density in campo rupestre was much lower than for other grasslands, species richness (92 seed morphospecies) was the highest reported in the literature. Higher seed density and species richness were captured in funnel traps, especially during the rainy season. Approximately 32% of morphospecies were registered exclusively in disturbed plots and 25% exclusively in preserved plots. This limited seed dispersability is of particular relevance for a better understanding of seed ecology and resilience in campo rupestre and may partially explain the poor recovery of these disturbed areas after soil removal.